ETHNOCULTURAL VALUES IN THE CONTEXT OF THE FESTIVAL MOVEMENT (Revista Inclusiones, 2021)
The article examines the festival movement as a subject of scientific research. On the basis of comparative and axiological methods, the author analyzes the influence of ethnocultural values on the formation of the cultural environment of the region. The functions, directions, forms and technologies of ethnocultural activity of festivals in the context of the national and cultural policy of the region are investigated. Shown are the tendencies in accordance with which the film-photoamateurism, folk art, and traditional values are developing in the festival movement.